In Vitro and In Vivo Dentinogenic Efficacy of Human Dental Pulp-Derived Cells Induced by Demineralized Dentin Matrix and HA-TCP - Kyung-Jung Kang; Min Suk Lee; Chan-Woong Moon; Jae-Hoon Lee; Hee Seok Yang; Young-Joo Jang (Stem Cells International)
Human dental pulp cells have been known to have the stem cell features such as self-renewal and multipotency. These cells are differentiated into hard tissue by addition of proper cytokines and biomaterials. Hydroxyapatite-tricalcium phosphates (HA-TCPs) are essential components of hard tissue and generally used as a biocompatible material in tissue engineering of bone. Demineralized dentin matrix (DDM) has been reported to increase efficiency of bone induction. We compared the efficiencies of osteogenic differentiation and in vivo bone formation of HA-TCP and DDM on human dental pulp stem cells (hDPSCs). DDM contains inorganic components as with HA-TCP, and organic components such as collagen type-1. Due to these components, osteoinduction potential of DDM on hDPSCs was remarkably higher than that of HA-TCP. However, the efficiencies of in vivo bone formation are similar in HA-TCP and DDM. Although osteogenic gene expression and bone formation in immunocompromised nude mice were similar levels in both cases, dentinogenic gene expression level was slightly higher in DDM transplantation than in HA-TCP. All these results suggested that in vivo osteogenic potentials in hDPSCs are induced with both HA-TCP and DDM by osteoconduction and osteoinduction, respectively. In addition, transplantation of hDPSCs/DDM might be more effective for differentiation into dentin.